Depression in pulmonary arterial hypertension: An undertreated comorbidity - Sameer Verma; Sonu Sahni; Vannan K Vijayan; Arunabh Talwar (Lung India, 2016)
Pulmonary arterial hypertension (PAH) is a debilitating condition leading to progressive decline in functional capacity. As a result, PAH can lead to psychological impairment that can impact the overall disease status. The medical community has developed several screening questionnaires in order to assess depression in their patients allowing physicians to be at the forefront of recognizing clinical depression. There is a suggestion that depression symptomatology is more prevalent in the PAH population. The aim of this article is to review the current thought process about diagnosis and management of depression in PAH patients.